Perlindungan Hukum Bagi Investor Pasar Modal Terkait Hilangnya Aset Nasabah Perusahaan Efek di Pasar Modal - Ifni Aqmarina; Ria Dolly Indra Wijaya Manurung; Elisa br. Tarigan; Leo Ronaldi Simbolon (Journal on Education, 2023)
The loss of investors' assets as customers of securities companies in the capital market has caused many people to still lack confidence in conducting fund transactions with securities companies. Even though the capital market is an effective way to improve the country's economy. The existence of several risks such as protecting investors' assets (fraud) can cause investors to suffer losses, lose valuable assets and disrupt the Indonesian capital market transaction climate. So that the protection of investor assets in Capital Market instruments is an important reason in assessing investment risk in Indonesia. This study aims to study the legal protection that provides corporate securities to customers and to analyze the weaknesses that occur due to the loss of corporate clients' securities assets so as to produce solutions. The method used is normative juridical method with descriptive analytical research specifications. The results of this research analysis are legal protection for capital market investors by SIPF, an institution managed by PT Indonesia Securities Investor Protection Program Organizer (P3IE) based on Decree of the Board of Commissioners of the Financial Services Authority Number Kep-43/D.04/2013. The Investor Protection Fund that has been collected has not been able to provide optimal protection both in terms of financing and the legal framework.